Exploring the potential of African higher education institutions in assisting the New Economic Partnership for Africa’s Development (NEPAD) to effectively achieve its goals - Iipumbu, Rebekka Nangula (Stellenbosch : Stellenbosch University, 2008)
The thesis explores the potential of African higher education institutions in assisting the New Economic Partnership for Africa’s Development (NEPAD) in its quest to affectively achieve its goals. My contention is that higher education institutions need to be favourably positioned in terms of institutional autonomy and academic freedom to assist the achievement of the NEPAD goals. Moreover, there is a need for deliberative democracy, if the NEPAD goals are to be achieved affectively, especially from the perspective of higher education institutions.